Natalie Zemon Davis, Listening to the Languages of the People. Lazar Sainéan on Romanian, Yiddish and French (Budapest: CEU Press, 2022), 200 pages - CRĂCIUN, Maria (Studia Universitatis Babeș-Bolyai Historia, 2025)
This discussion concerning Natalie Zemon Davis’ book, Listening to the Languages of the People: Lazar Sainéan on Romanian, Yiddish and French could begin by asking: What’s in a name? This particular question would be inspired by the fact that the book’s main protagonist is Lazăr Şăin, who became Lazăr Şăineanu and later Lazare Sainéan, bringing to the fore the transformations, the refashioning, that a change of name could elicit. The book, acknowledged as a biography by its author, relies partly on an autobiographical essay written by Şăineanu in 1901, when he had decided to leave Romania, and partly on several other sources, mainly reviews of Şăineanu’s work, written by his contemporaries, friends, enemies, scholars, politicians and renown public figures. Starting from this enmeshing of stories, the one written by the subject and the one pieced together by his biographer, this review would like to start a discussion about narrative, the function of narrative in the field of history and the role of one well-documented biography as illustration for the mood of an era.[1] This attempt will be framed by a larger issue, bringing into question the value of a story, in this case a biography, as a source in the writing of history. [1] The return to narrative has been discussed by Lawrence Stone, “The Revival of Narrative: Reflections on a New Old History,” Past and Present, 85 (1997): 3-24; James West Davidson, “The New Narrative History. How New? How Narrative?,” Reviews in American History, 12/3 (1989): 322-334; Peter Burke, “History of Events and the Revival of Narrative,” in New Perspectives on Historical Writing (Cambridge: Polity Press, 1992) suggests that historians should borrow the anthropological principle of thick description, which integrates story and context.